Keeping an eye out for Klebsiella endopthalmitis: Klebsiella pneumoniae invasive liver abscess syndrome - Jia, Ying S; Ian, Chik; Azlanudin A,; Zamri Zainal,; Hairol O, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Hypervirulent Klebsiella pneumoniae strain is a major cause of liver abscess and this bacteria has metastatic properties. This distinct liver abscess syndrome has been increasingly reported in Asia over the past two decades, but is emerging as a global disease. We described an 81-year-old lady, who presented to the emergency department with 1-week prior duration of fever and right eye swelling. She had been admitted for recurrent liver abscess prior to this. Hence, she was initially treated as sepsis secondary to recurrent liver abscess. Meanwhile, she was managed concurrently by ophthalmology team for endophtalmitis. Despite the initiation of treatment with antibiotics, she did not show any improvement and required right eye evisceration to treat the sepsis. Invasive liver abscess syndrome with metastatic endophthalmitis should be screened in patient with Klebsiella liver abscess. They should be monitored for ocular symptoms as early recognition can prohibit delays in treatment, which has debilitating consequences.